Shells of Telescopium Telescopium as Biomonitoring Materials of Ni Pollution in the Tropical Intertidal Area - C. K. Yap (Institute of Advanced Engineering and Science, 2014)
The objective of this paper is to propose the use of the shells of Telescopium telescopium as good biomonitoring materials of Ni pollution. The snail and surface sediment samples were collected from 17 geographical sites in Peninsular Malaysia and they were dissected into six different soft tissues, namely foot, cephalic tentacle (CT), mantle, muscle, gill and remaining soft tissues (REST). The total shells, pooled and dissected soft tissues and sediments were determined for Ni using an air-acetylene flame Atomic Absorption Spectrophotometer. The present findings based on 1) ratios of shell/soft tissues (ratios> 1.0), 2) bioaccumulation factor values (shell as microconcentrator), 3) statistical outcomes of correlation analysis [significant correlations between shells and geochemical fractions (acid-reducible, non-resistant, resistant and total Ni concentrations) in the environmental sediments] and multiple linear stepwise regression analysis [significantly influenced by total Ni concentrations in the sediment], and 4) lowest value of coefficient of variation [thus higher precision], do indicate the very potential of shells of T. telescopium as good biomonitoring material of Ni pollution in the tropical intertidal area.